Good Girls: Season 1 - Hendricks, Christina, 1975-; Retta; Whitman, Mae, 1988-; Montana, Manny; Universal Pictures Home Entertainment (Firm) (Universal City, CA : Universal Pictures Home Entertainment, 2018)
Three suburban moms rob a supermarket to provide for their families, but they find themselves in hot water when they learn it's run by a local gang. - imdb.com.
Pilot -- Mo money, mo problems -- Borderline -- Atom bomb -- Taking care of business -- A view from the top -- Special sauce -- Shutdown -- Summer of the shark -- Remix.
Originally broadcast as single episodes of a television program in 2018.
Wide screen (1.78:1).
New DVD Fall 2023.
Christina Hendricks, Retta, Mae Whitman, Manny Montana, Reno Wilson, Lidya Jewett, Matthew Lillard.
Rating: Not rated.
DVD, region 1, NTSC, wide screen (1.78:1); Dolby Digital 5.1.
Keywords: Mothers -- Drama; Crime -- Drama; Robbery -- Drama; Crime television programs; Video recordings for the hearing impaired